A Miracle Obstetrical Result: Iso-immunized Baby with HighTiter with Good Foetal Outcome - RC, LK (Nepal Journal of Obstetrics and Gynaecology, 2015)
We present a case of 26 years multigravid women (G2PoLoA1) with iso-immunized foetus with high titre 1:512, delivered at 36+6 weeks of pregnancy. She visited the hospital in the second trimester of pregnancy for routine antenatal check up. There was a past history of spontaneous abortion at 12 weeks where no immunoglobulin (rhogam) injection was taken. At 22+ weeks of gestation, she was admitted in the hospital with titre 1:128 and 1:512. Counseling was done for outcome of foetus and advised for termination, but parents wanted to continue the pregnancy. Dexamethasone injection was given for foetal lung maturity and then discharged. Baby was kept in the nursery and double phototherapy was given and discharged at the seventh day of life.